Peningkatan Kualitas Belajar Melalui Kegiatan Inovatif Pada Anak-Anak di Dusun Sagi Desa Tarokan - Erdiana, Fairus Salsabila; Sukeshi, Opin; Ubbad, Mohammad Rofi’ul (Fakultas Tarbiyah IAIN Kediri, 2024)
This research aims to: (1) Identify the third program (Tutoring, Reading Corner, Ecoprint) in improving the quality of education and welfare of the people of Sagi Hamlet and document these activities which can be an inspiration for other villages with similar conditions. (2) Provide insight into how to increase children's academic capacity through tutoring, develop interest in reading through reading corners, and economic empowerment and environmental awareness through ecoprint training to achieve sustainable results. (3) Can be a reference in designing and implementing similar programs in other regions. This research was conducted using the ABCD (Asset-Based Community Development) method. The research subject was a resident of Tarokan Village, Kediri Regency and the sample for this research was the children and youth of Sagi Hamlet, Tarokan Village, Kediri Regency, totaling 80 people. Data collection techniques use documentation in the form of photos. The results of the analysis of the Optimization of Educational Potential in Tarokan Village, Kediri Regency show that there is an influence on the Tutoring Program, Reading Corner and Ecoprint Training, namely by increasing the enthusiasm for learning of Children and Youth in Sagi Hamlet.